Less Mainstream Credit, More Payday Borrowing? Evidence from Debt Collection Restrictions - FONSECA, JULIA (Journal of Finance, 2023)
ABSTRACT Governments regulate debt collectors to protect consumers from predatory practices. These restrictions may lower repayment, reducing the supply of mainstream credit and increasing demand for alternative credit. Using individual credit record data and a difference‐in‐differences design comparing consumers in states that tighten restrictions on debt collection to those in neighboring states that do not, I find that restricting collections reduces access to mainstream credit and increases payday borrowing. These findings provide new evidence of substitution between alternative and mainstream credit and point to a trade‐off between shielding consumers from certain collection practices and pushing them into higher cost payday lending markets.